Gamma Delta (γδ) T Cells and Their Involvement in Behçet’s Disease - Md. Samiul Hasan; Lesley Ann Bergmeier; Harry Petrushkin; Farida Fortune (Journal of Immunology Research)
Behçet’s disease (BD) is a multisystem inflammatory disorder characterized by orogenital ulcerations, ocular manifestations, arthritis, and vasculitis. The disease follows a relapsing-remitting course and its pathogenesis is unknown. Genetic predisposition and immune-dysregulation involving gamma delta (γδ) T cells are reported to have a role. γδ T cells are atypical T cells, which represent a small proportion of total lymphocytes. They have features of both innate and adaptive immunity and express characteristics of conventional T cells, natural killer cells, and myeloid antigen presenting cells. These unconventional T cells are found in the inflammatory BD lesions and have been suggested to be responsible for inducing and/or maintaining the proinflammatory environment characteristic of the disease. Over the last 20 years there has been much interest in the role of γδ T cells in BD. We review the literature and discuss the roles that γδ T cells may play in BD pathogenesis.